2022
DOI: 10.3390/su14137708
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water Quality Change on the Corrosion Process in Galvanized Pipes of Fire Protection Installations

Abstract: The article presents the results of an investigation of water composition and quality in sprinkler installations, as well as the influence of temperature changes on the corrosion process. The physical and chemical components of the water were measured to ascertain the influence of its properties on the corrosion process in a wet pipe sprinkler system operating in significantly changing ambient temperature conditions. The article presents the results of measurements of the wall thickness of galvanized pipes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The RSIs obtained in the rivers were all above 8.5 (RSI > 8.5) indicating that the water is rigorously corrosive [37]. The neutral zone of the Ryznar index is more or less the numerical value of six according to Wojtkowska et al [65]. The Larson-Skold Index result revealed that all the water types assessed were severely corrosive (LS > 1.2) and the ratio of the concentration of chloride and sulfate ions to the concentration of bicarbonate and carbonate ions will interfere with natural film formation (LS > 0.8).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The RSIs obtained in the rivers were all above 8.5 (RSI > 8.5) indicating that the water is rigorously corrosive [37]. The neutral zone of the Ryznar index is more or less the numerical value of six according to Wojtkowska et al [65]. The Larson-Skold Index result revealed that all the water types assessed were severely corrosive (LS > 1.2) and the ratio of the concentration of chloride and sulfate ions to the concentration of bicarbonate and carbonate ions will interfere with natural film formation (LS > 0.8).…”
Section: Discussionmentioning
confidence: 90%
“…The RSI obtained in the rivers were all above 8.5 (RSI > 8.5) indicating that the water is rigorously corrosive [37]. The neutral zone of the Ryznar index is more or less the numerical value six according to Wojtkowska et al [65]. Generally, any value above six indicates that the water is likely to form a CaCO 3 scale.…”
Section: Scaling and Corrosivity Tendencies And Spatial Distribution ...mentioning
confidence: 91%
See 1 more Smart Citation